Internationale Metallarbeiter-Rundschau : . International Metalworkers' Review. Off. organ of the International metalworkers' Federation (I.M.F.)
Text in English, French and German. - (1916) split into different publications: Internationale Metallarbeiter-Rundschau. Off. Organ ... (ZK 16030). - Revue internationale des ouvriers sur metaux. Organe officiel ... (ZK 16030 A). - Continued by: Mitteilungsblatt des Internationalen Metallarbeiterbundes (I.M.B.) (ZK 16031).